Science and the Navy : the History of the Office of Naval Research. - Sapolsky, Harvey M. (Princeton legacy library., 2014)
Addressing all those interested in the history of American science and concerned with its future, a leading scholar of public policy explains how and why the Office of Naval Research became the first federal agency to support a wide range of scientific work in universities. Harvey Sapolsky shows that the ONR functioned as a ""surrogate national science foundation"" between 1946 and 1950 and argues that its activities emerged not from any particularly enlightened position but largely from a bureaucratic accident. Once involved with basic research, however, the ONR challenged a Navy skeptical.